Analysis of the Concepts and Regulations of Sharia Accounting in Sharia Insurance Transactions in Indonesia - Alia Rohali; Nur Citra Hasanah; Rahmad Syah Aldi; Intan Permata Sari Br. Siburian; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
The rapid development of the world economy has produced various companies and financial institutions in Indonesia, both banks and non-banks. In line with this development, it also triggers the thinking of the Muslim community about the existence and activities of companies and financial institutions. The Muslim community doubts the activities of financial institutions, so that financial institutions with a sharia basis are established. However, the rapid development of Islamic financial institutions also triggers the community to treat their accounting the same as other conventional financial institutions, so that the sharia accounting system is established for Islamic financial institutions. In this case, the author discusses the sharia accounting system in Islamic insurance using a research method of the type of study whose data is taken from books to scientific journals. The results of the discussion that the author obtained in this article's research are that Islamic accounting is the process of recording, classifying, summarizing and reporting finances in a company during a certain period that refers to Islamic law. The accounting system in sharia-based insurance is found in its treatment, its principles, namely justice, and its application. Unlike accounting in general, Islamic accounting prioritizes sharia principles. the application of accounting in sharia insurance, one of which is recognized in the financial statements of the next period if the acquisition of the insurance premium occurs before the transaction date. From these results, the author concludes that sharia insurance has implemented accounting in accordance with Islamic law, namely sharia accounting. This sharia accounting is very important in making financial reports in sharia insurance and also other sharia institutions. The more we understand the concept of sharia accounting, the better the reporting we will make.